Conservation practices for weed management in upland rice- based cropping system - Durga, C.; Anitha, S. (Journal of Tropical Agriculture, 2023)
A field experiment was carried out at Agronomy Farm, College of Agriculture, Vellanikkara from May 2019 to March 2021. The study was laid out in randomized block design, to develop conservation agriculture practices for upland rice-vegetable-green manure cropping system. It was found that different conservation agriculture strategies significantly impacted weed management compared to rice grown without any conservation agriculture practices. The total weed density and weed dry matter production were lower in direct seeded rice in flat bed+ brown manuring (11.47no/m2 ), which was on par with direct seeded rice in flat bed+ green manuring (11.55no/m2 ), and higher in direct-seeded rice alone in flat bed (21.83no/m2 ) at 30DAS, and a similar trend was followed in 60 DAS and at harvest. Rice grown alone in raised bed recorded the lowest weed density and had a 28-39% reduction in weeds compared to rice grown alone in flat bed. A high grain yield of 3047.50 kg/ha and a B:C ratio of 2.59 was recorded in direct seededrice in flat bed+ green manuring. The lowest yield of 1540 kg/ha and lowest B:C ratio of 1.13was observed in direct seeded rice grown alone in a flat bed without any conservation agriculture practices.